Christmas Eve at Friday Harbor [large type] - Kleypas, Lisa (Kleypas, Lisa. Friday Harbor novel., 2010)
Three lonely people, three lives at crossroads, three people who are about to discover that Christmas is a time when anything is possible and when wishes can come true.